Soil aggregation and erodibility indices under different land uses in Jorhat district of Assam - DUTTA, NAMITA; DUTTA, SAMIRON; KARMAKAR, R. M (Journal of Soil and Water Conservation, 2020)
Present investigation was conducted in soils under four different land uses viz. rice field, upland vegetable growing land, tea plantation area and natural forest land of Jorhat district, Assam to study the effect of land use on soil aggregation and erodibility. Soils varied in their physico-chemical properties such as texture, organic carbon, pH, CEC etc. Soils under natural forest and tea plantation exhibited the almost equal amount of water stable aggregate (weighted mean of profile 57.63 and 57.56 %) followed by rice soil (53.67%) and vegetable growing area (44.93%). The macroaggregates of the soils varied from 30.12 to 66.97 % and it was highest in rice soil (weighted mean 45.63 %) followed by tea plantation area and natural forest (38.96%) and vegetable growing area (30.99%). Microaggregate was found lowest in rice soils (weighted mean, 8.05%) and vegetable growing areas showed an intermediate value of 13.94%. It ranged from 4.10 to 24.02% which is significantly lower than the amount of macroaggregates. Highest value of mean weight diameter was found under forest land (3.30mm) and vegetable soil has the least value (0.30mm). Soil erodibility was measured through Dispersion ratio and Erosion ratio which varied from 14.1 to 31.8 and 7.29 to 19.38 respectively in the soils. Considering dispersion ratio and erosion ratio, erodibility of the soils was in the order rice soil > vegetable soil > tea soil > forest soil. Organic carbon and total exchangeable cations were found to be the most dominant factors contributing in soil aggregation in soils under all the land use systems